Italy : Background Economic Developments and Issues. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews developments in the Italian economy during 1994 with some special attention to some specific issues. It describes trends in the real economy, with special annexes focusing on the outlook for inflation and the response of employment to cyclical and structural factors. The paper discusses fiscal developments, and summarizes developments in the monetary sector. It also reviews empirical evidence on money demand in Italy, and the combination of cyclical and structural factors impinging on the banking system.